Estimating insertion length of umbilical arterial and venous catheters in newborn infants: time for change. (2nd October 2022) - Stuttaford, Laura; Webb, Jennifer; Smith, Susan L.; Powell, Colin; Watkins, William J.; Chakraborty, Mallinath
Abstract: Background: Umbilical catheters are inserted through the umbilical artery or vein at birth and are crucial in neonatal care. There are several different methods of estimating adequate insertion length of umbilical catheters based on one of two hypotheses; that the insertion length of the UC is correlated to either the infant's birth weight or an external length measurement. Aim: To review the published literature on methods of estimating insertion lengths of umbilical arterial catheters (UACs) and umbilical venous catheters (UVCs) in newborn infants. Methods: Systematic search on Medline was undertaken using keywords for relevant papers up to March 2019. Papers were selected by manual search of titles and abstracts. Results: Formulae for predicting umbilical catheter insertion length are unreliable, particularly for UVCs. There is also conflicting evidence around whether birth weight-based formulae are more reliable than external length-based formulae. Studies comparing various methods to determine their efficacy to show that current formulae have a low accuracy for determining both UVC and UAC positioning. Conclusions: Current formulae for estimating insertion length of umbilical catheters are not fit for purpose. We propose a new observational study which uses a new external length measurement, the sternal notch to umbilicus length, to develop a more reliable formula for the insertion of UVC and UAC to an adequate length.